Analisis Perbandingan Badan Hukum Sebagai Direktur Perseroan Terbatas di Britania Raya dan Indonesia - Firdaus, Khalid Archie (Universitas Ekasakti, 2023)
This comparative study examines the regulations and implications of allowing Legal Persons to serve as directors in Limited Liability Companies (LLCs) in the United Kingdom and Indonesia. The legal framework governing LLCs in Indonesia is explored, with a focus on the role of the General Meeting of Shareholders, Board of Directors, and Board of Commissioners. The study highlights the evolution of Indonesian corporate law, influenced by both civil law and common law. In the United Kingdom, the study delves into the Companies Act 2006, which allows for Legal Persons to be appointed as directors alongside Natural Persons. It discusses the history of the concept of separate legal personality and limited liability in company law, drawing parallels between Indonesian and UK legal systems. The research further delves into the prohibition of Corporate Directors in the UK introduced through the Small Business, Enterprise and Employment Act 2015 and examines the reasons for this prohibition, including concerns related to transparency and accountability. The study assesses the status of this prohibition and the proposed exceptions, emphasizing the importance of balancing business efficiency with regulatory safeguards. In conclusion, the study suggests that Indonesia could consider regulations regarding the inclusion of Corporate Directors in LLCs but emphasizes the need for stringent limitations to prevent misuse, opacity, and financial crime. The research highlights the ongoing legislative process in the UK and recommends that Indonesian regulations on Corporate Directors should be tailored to promote efficient business growth while maintaining transparency and accountability.